Relationship of Digital Game Addiction with Aggression and Anger in the Post COVID-19 Era: A Systematic Review and Meta-Analysis - Nagar, Kaushal; Kumar Patidar , Anil; Kumar Mudgal, Shiv; Gaur, Rakhi; Patidar, Vipin (Investigación y Educación en Enfermería, 2025)
Objectives. To evaluate the relationship of digital gaming addiction with aggression and anger behavior among people. Methods. This meta-analysis and systematic review was conducted using PRISMA and MOOSE guidelines to find articles in the databases PubMed, Scopus, Embase, and EBSCO. The evaluation comprised ten studies with 11,259 individuals. Researchers systematically extracted data on aggression, anger, and gaming addiction. The meta-analysis evaluated heterogeneity and pooled correlations using random-effects models. The study protocol was registered with PROSPERO under the registration number CRD42025642494. Results. Addiction to digital games was found to be strongly correlated with aggression (r = 0.531, 95% CI [0.226, 0.836]) and moderately with anger (r = 0.348, 95% CI [0.177, 0.518]). Regional analysis revealed that Saudi Arabia study had the strongest correlation (β = 1.004, p<0.001), whereas Italy, Nepal, Singapore, and Turkey studies had comparatively lower correlations. Anger consequences were also found to be moderated correlations by age, with younger adolescents experiencing more negative consequences (β = -0.0696, p=0.049). Conclusion. The meta-analysis demonstrates significant positive correlations between digital game addiction, aggression, and anger, highlighting the importance of nurse-led interventions in vulnerable groups in order to promote the reduction of the negative consequences of digital addiction.